Educational level and verbal expressive language in the elderly: The mediating role of episodic verbal memory - Medina-Valdebenito, Damian; Cancino , Vicente (Revista de Investigación en Logopedia, 2024)
Life expectancy worldwide has increased considerably in the last few decades. Likewise, it has been shown that educational level is one of the most influential factors in general cognition as well as in the development of cognitive impairment. It has also been shown that both verbal expressive language (VEL) and verbal episodic memory (VEM) are cognitive abilities that may change during the aging process. The aim of this study was to determine the relationship between educational level and VEL and whether this relationship is mediated by VEM in older people. Educational level, VEL, and VEM were assessed in a sample of 206 Chilean elderly persons (X̅ 69 years; S.D. = 7.2). A direct and significant effect of educational level on both VEL (β = 0.438, p < .001) and VEM (β = 0.411, p < .001) was found, as well as a direct effect of VEM on VEL (β = 0.634, p < .001). In addition to this, a significant mediation through VEM was identified (β = 0.268, p < .001). It is concluded that educational level is a contributing factor to neuroprotective in older people and predicts performance on VEM and VEL. Likewise, a partial mediation of VEM in the relationship between educational level and VEL is identified.
Keywords: Verbal expressive language; aging; educational level; verbal episodic memory